Kesalahan Pemilihan Bunkei dalam Soal Shoutesuto Mata Kuliah Enshuu 2 - Zuliastutik, Hendri; Nugroho, Rahadiyan Duwi; Armita, Eki Danah (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2023)
This study describes the mistakes in choosing bunkei and the causes of mistakes made by second-level students of Japanese Literature Study Program, University of Dr. Soetomo in answering the Enshuu 2 quiz questions chapters 26 to chapter 34. The theory used in this study is the theory of language errors and the theory of bunkei in chapters 26-34. The benefits of this research are expected to be material for evaluating the learning of respondents and Japanese language learners in understanding the bunkei properly and correctly, and can be a reference for teachers in explaining bunkei in class in more detail. This study uses a qualitative method. The data is in the form of sentence pattern questions or bunkei shoutesuto Enshuu 2 where the answer choices are wrong with more than 4 voters added to the respondent's answer questionnaire. Based on the analysis, the respondents’ selection errors in selecting bunkei that were most frequent to least were bunkei …nai de,… …te…masu, …hou ga ii, …kanoukei forms (forms of ability) […raremasu], …ga miemasu/ … ga kikoemasu, …deshou, mada …te imasen, and ..te shimaimamashita. The cause of the error was because the respondent still did not understand the context of the question sentence properly and was not careful. keywords: bunkei; Enshuu 2; language errors; shoutesuto.